Cardiac-specific deletion of GCN5L1 restricts recovery from ischemia-reperfusion injury. (April 2019) - Manning, Janet R.; Thapa, Dharendra; Zhang, Manling; Stoner, Michael W.; Traba, Javier; McTiernan, Charles F.; Corey, Catherine; Shiva, Sruti; Sack, Michael N.; Scott, Iain
Abstract: GCN5L1 regulates mitochondrial protein acetylation, cellular bioenergetics, reactive oxygen species (ROS) generation, and organelle positioning in a number of diverse cell types. However, the functional role of GCN5L1 in the heart is currently unknown. As many of the factors regulated by GCN5L1 play a major role in ischemia-reperfusion (I/R) injury, we sought to determine if GCN5L1 is an important nexus in the response to cardiac ischemic stress. Deletion of GCN5L1 in cardiomyocytes resulted in impaired myocardial post-ischemic function and increased infarct development in isolated work-performing hearts. GCN5L1 knockout hearts displayed hallmarks of ROS damage, and scavenging of ROS restored cardiac function and reduced infarct volume in vivo. GCN5L1 knockdown in cardiac-derived AC16 cells was associated with reduced activation of the pro-survival MAP kinase ERK1/2, which was also reversed by ROS scavenging, leading to restored cell viability. We therefore conclude that GCN5L1 activity provides an important protection against I/R induced, ROS-mediated damage in the ischemic heart. Highlights: GCN5L1 is a key regulator of mitochondrial protein acetylation, biogenesis and organelle positioning. Loss of GCN5L1 in the heart promotes mitochondrial reactive oxygen species production, leading to cell death. Treatment of GCN5L1-depleted hearts or cardiac cells with antioxidants prevents cell death following ischemic injury. Loss of protective ERK1/2 signaling is evident in GCN5L1-depleted cardiac cells, and is restored by antioxidant treatment.